Steatohepatitis Is Not Associated with an Increased Risk for Fibrosis Progression in Nonalcoholic Fatty Liver Disease - Hannes Hagström; Olof Elfwén; Rolf Hultcrantz; Per Stål (Gastroenterology Research and Practice)
Introduction. Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease globally. The majority of NAFLD patients have fatty liver without inflammation (nonalcoholic fatty liver, NAFL), whereas a minority develop steatohepatitis (nonalcoholic steatohepatitis, NASH). Only NASH and not NAFL has been considered to increase the risk for fibrosis progression. The present study investigates risk factors for fibrosis progression in patients with NAFLD, and if fibrosis progression associates with subsequent mortality. Material and Methods. All patients with at least two liver biopsies more than a year apart at our hospital between 1971 and 2016 were identified. Data on plausible risk factors for fibrosis progression were collected. Biopsies were scored for the presence of NASH and fibrosis stage. Regression models were used to investigate the association between baseline NASH and fibrosis progression and fibrosis progression with future mortality. Results. 60 patients had undergone serial biopsies (median interval between biopsies 8.4 years, range 1–33 years), with 26 patients (43%) having fibrosis progression. We found no significant risk factors for progression of fibrosis except time between biopsies. Among patients with fibrosis progression, 54% had NAFL and 46% had NASH at baseline. There was a trend for an association between fibrosis progression per se and increased mortality (hazard ratio 2.83, 95% CI 1.0–8.1, p=0.05). Conclusions. In this study on NAFLD, baseline steatohepatitis was not associated with an increased risk for fibrosis progression. NAFLD patients without steatohepatitis may develop progressive fibrosis, and those with progressive fibrosis appear to have a higher mortality risk irrespective of baseline NASH status.